2002
DOI: 10.1159/000064139
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Resection of a Juvenile Angiofibroma Using an Ultrasonically Activated Scalpel

Abstract: We report a case of juvenile nasopharyngeal angiofibroma (JNA). A 19-year-old male came to our clinic complaining of severe nasal obstruction and epistaxis. Imaging investigations using computed tomography and magnetic resonance imaging techniques revealed a soft tissue mass in the nasopharynx with minimal extension to the pterygopalatine fossa. After embolization of the internal maxillary artery, we successfully performed endoscopic transnasal surgery for a JNA using an ultrasonically activated scalpel. Endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Including the present series, approximately 100 cases of JA treated by endonasal approach have been reported in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] ; thus, this procedure cannot be considered as a "standard" technique. Therefore, patients who undergo such a treatment require careful follow-up evaluation for the early detection of possible residual lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Including the present series, approximately 100 cases of JA treated by endonasal approach have been reported in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] ; thus, this procedure cannot be considered as a "standard" technique. Therefore, patients who undergo such a treatment require careful follow-up evaluation for the early detection of possible residual lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical options, including transhyoid, transpalatal, transfacial (through a lateral rhinotomy or a midfacial degloving), and infratemporal approaches, have been advocated. Recent reports have focused on more conservative transnasal treatments, using either purely endoscopic 5–20 or combined microscopic–endoscopic techniques. 21,22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Many authors have reported their preliminary experiences of the removal of such tumours, either endoscopically or endoscope-assisted following conventional surgery. 4 -24 Endoscopic tumour removal can be assisted by electrocautery, 3,22 laser, 15,19 ultrasonic activated scalpel, 17 image-guided surgery and frozen section pathological analysis. 19 We report our experience of endoscopic exposure and excision of juvenile nasopharyngeal angiofibroma.…”
Section: Introductionmentioning
confidence: 99%
“…9 The ultrasonically activated scalpel is effective at providing good hemostasis and minimizing injury to important structures, 5 and it is more effective in preventing bleeding than stopping bleeding. 24 This device provided better visualization of the operative field, with the absence of smoke, char, and odor. 5 The backside of the hook blade was usually used for the dissection; however, the coagulating shears were used when bisecting the vascular structures.…”
Section: Discussionmentioning
confidence: 99%